Anaemia among women of reproductive age in selected sub-Saharan African countries: multivariate decomposition analyses of the demographic and health surveys data 2008–2018 - Salifu, Mohammed Gazali; Da-Costa Vroom, Frances Baaba; Guure, Chris (Frontiers in Public Health, 2024)
Objectives The burden and highest regional prevalence of anaemia is reported in sub-Saharan Africa (SSA). The study evaluated changes in anaemia prevalence across the Demographic Health Surveys (DHS) periods in SSA and reported factors influencing observed changes in the trend. Method The study was implemented by a two-stage cross-sectional stratified sampling approach. The study involved women of reproductive age (15–49 years) in sub-Saharan Africa countries (Ghana, Sierra Leone, Mali, and Benin) using two different periods of their demographic health surveys (DHS) data. The study adopted both descriptive and inferential statistical methods. The chi-square test was used to determine the existence of a statistically significant relationship between the outcome and predictor variables and test the observed changes in anaemia. Multivariable logistic regression analyses were conducted on each survey year and the pooled dataset for eligible study countries. Multivariate decomposition analysis was performed to explain how compositional changes and behavioural effects of women characteristics affected the changes in anaemia prevalence. The study reported frequencies, percentages and odds ratios along with their 95% confidence intervals (CI). Results Ghana and Sierra Leone experienced 17.07% [95% CI: 14.76–19.37, p < 0.001] and 1% [95% CI: 1.0–2.9, p > 0.05] of anaemia decrease from period 1 to period 2, respectively, while Mali and Benin experienced 11% [95% CI: 9.14–12.90, p < 0.001] and 16.7% [95% CI: 14.99–18.5, p < 0.001] of increase in anaemia prevalence from period 1 to period 2, respectively. Behavioural effects explained the decrease in Ghana and the increase in Benin and Mali while endowments or compositional changes explained the decrease in Sierra Leone. Conclusion Anaemia continues to pose a significant challenge in sub-Saharan Africa. Therefore, there is an imperative need to scale up the implementation of nutrition-related programmes and advocacies to ensure optimum changes in women nutrition-related behaviours.